The Screwtape letters : with Screwtape proposes a toast - Lewis, C. S. (Clive Staples), 1898-1963.; Lewis, C. S. (Clive Staples), 1898-1963 (San Francisco : HarperSanFrancisco, 2001)
In this humorous and perceptive exchange between two devils, Lewis delves into moral questions about good vs. evil, temptation, repentance, and grace.--From publisher description.
Originally published: 1st Touchstone ed. New York : Simon & Schuster, 1996.
Keywords: Christianity -- 20th century